MITIGATION OF LANDSLIDE PRONE AREAS IN ANTICIPATION OF CLIMATE CHANGE IMPACTS - Priyono; Triatmojo, Siswadi; Rahayu (jfpublisher, 2023)
In general, landslides occur when the upward slope is higher than the retaining force which is caused by high rainfall intensity, land slope, load and impermeable layer, soil solum thickness, and soil type. The restraining force is generally controlled by the resistance of soil shear, the density and strength of plant roots and the strength of rocks. This disaster also often occurs in Indonesia, which has many mountains that stretch across the country. This research aims to determine landslide-prone areas, landslide types, dominant factors that cause landslides and landslide mitigation in anticipation of the impact of non-structural climate change. The research included 3 stages, such as pre-field, field, and post-field which are interrelated and complementary. The research location is around landslide-prone lands along the southwest slope of Mount Lawu in Karanganyar Regency, Central Java. Based on the results of the research analysis, it indicates that the southwest slope of Mount Lawu, especially in Karanganyar, is highly prone to landslides. Therefore, it is not suitable to be used as agricultural and residential land because of its area of about 6,797.06 ha, and is categorized into three crucial parts, such as areas that are still highly prone to landslides of about 5,005.35 ha (73.64%); landslide-prone area of 1,784.23 ha (26.25%); and slightly landslide-prone area of 7.48 ha (0.11%).